2013
DOI: 10.1007/s00586-013-3091-z
|View full text |Cite
|
Sign up to set email alerts
|

Incidental dural tear in spine surgery: analysis of a nationwide database

Abstract: Purpose The purpose of this study was to report the incidence of dural tear (DT) in spine surgery, risk factors, and patient outcomes on a national level. Methods Clinical data were obtained from the Nationwide Inpatient Sample for 2009. Patients who underwent spine surgery were identified and, among them, patients who had DT were identified, according to the International Classification of Diseases, 9th revision, Clinical Modification (ICD-9-CM) codes. Patient and hospital demographic data were retrieved. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 22 publications
4
30
2
1
Order By: Relevance
“…This fact may be attributed mainly to differences in patient cohorts as well as the types of surgical procedures and indications. The majority of these previously published studies reported the overall incidence of dural lacerations across a variety of spinal surgeries [10,12,19,20], such as combined fusion and decompression procedures [7,9,11,21]. For lumbar disc surgery, the previously published incidences of dural tears seem to be relatively low, with reports ranging between 2 and 6 % [22,23].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This fact may be attributed mainly to differences in patient cohorts as well as the types of surgical procedures and indications. The majority of these previously published studies reported the overall incidence of dural lacerations across a variety of spinal surgeries [10,12,19,20], such as combined fusion and decompression procedures [7,9,11,21]. For lumbar disc surgery, the previously published incidences of dural tears seem to be relatively low, with reports ranging between 2 and 6 % [22,23].…”
Section: Discussionmentioning
confidence: 96%
“…This variation may be attributed to the fact that some studies include all types of lumbar spine surgeries, while other studies focus on decompression procedures exclusively. Risk factors for the occurrence of an incidental durotomy include epidural adhesions associated with previous surgeries, synovial cysts, severe spinal stenosis, increased comorbidities, smoking, and increased patient age [8][9][10][11][12]. Previously published studies investigated whether an incidental durotomy is associated with an inferior outcome after lumbar decompression surgery.…”
Section: Introductionmentioning
confidence: 93%
“…The Elixhauser measure has not been introduced in orthopaedic surgery research until recently [17,26,39,57,59,60], perhaps because of scarce reported comparisons with the Charlson model [17] and concerns regarding the inclusion of too many explanatory variables (31 variables), therefore requiring a relatively large sample size [27]. The main attractiveness of the use of large administrative databases for medical research lies in the possibility of studying rare occurrence events, such as inpatient mortality, that otherwise would be difficult to investigate in small population studies [14].…”
Section: Discussionmentioning
confidence: 99%
“…Arrhythmias are associated with a worse course of anaphylaxis owing to mechanisms other than those involved in congestive heart failure, since the distribution of both variables differed. The appearance of heart block and arrhythmias may be related to myocardial hypoxia during anaphylaxis [24,26] or local secretion of noradrenaline from sympathetic nerve endings resulting from secretion of renin from mast cells and activation of the renin-angiotensin system [21]. The evidence presented above suggests that arrhythmias follow the onset of anaphylaxis.…”
Section: Discussionmentioning
confidence: 98%
“…The presence of mast cells in the heart and the release of cardiotoxic mediators such as histamine, LTC4, and platelet-activating factor [21], as well as the increase in mast cell counts in the coronary vessels of patients with ischemic heart disease, can render the heart incapable of overcoming the systemic and cardiac effects of anaphylaxis. In addition, the widespread concomitant use of β-blockers and ACE inhibitors in cardiovascular diseases [22,23] has been considered to cause more severe anaphylaxis in patients with heart disease [24].…”
Section: Discussionmentioning
confidence: 99%